Attitudes of Healthcare Team towards Interprofessional Collaboration - Roya Botshekanan; Simin Tahmasbi (Journal of Social Behavior and Community Health, 2025)
Background: Inter-professional collaboration (IPC) is vital in enhancing the quality of healthcare. Hence, this study aims to evaluate the attitudes of healthcare staff towards interprofessional cooperation. Methods: The study utilized a descriptive-analytical method. The medical teams from two hospitals of Shahrekord University, constituted the study population. Using stratified sampling, 325 individuals were selected.on 2020  Data were gathered by Jefferson Interprofessional Attitude Questionnaire, consisting of demographic information and IPC questions (20 items.. SPSS (20) was used for data analysis, and variables were assessed by descriptive tests, one-sample t-tests, t-student tests, Levene tests, and ANOVA. Results: The mean scores for attitudes towards IPC were as follows: general practitioners (4.54 ± 0.31), specialists (4.94±0.37), nurses (4.84±0.40), midwives (4.86±0.36), radiologists (4.86±0.43), nutritionists (4.69±0.46), laboratory staff (4.97±0.38), pharmacists (4.99±0.49), operating room anesthesiologists (5.09 ±0.38), environmental and occupational health experts (5.07±0.35), and psychologists (5.19±0.34). There was a significant difference (p < 0.05) between general practitioners and anesthesia and operating room experts. The relationship between demographic data with mean score of IPC was not significant, but it was significant forjob experience of 15-20 years (sig = 0.001 and F = 8.81). Conclusion: Managers should promote a positive attitude towards IPC within the healthcare team. By implementing an educational strategy, cooperation and performance among healthcare staff can be enhanced.